2023
DOI: 10.3389/fpsyg.2023.1154657
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the use of videoconference by and for older adults in nursing homes: an interdisciplinary approach to learn from the pandemic

Abstract: IntroductionDuring the Covid-19 pandemic and the resulting visitation restrictions, digital tools were used in many nursing homes in France to allow the older adults and their relatives to maintain social contact via videoconferencing. This article adopts an interdisciplinary approach to analyze the processes that affect the use of digital technologies.MethodsDrawing on the concept of “mediation,” it seeks to shed light on how individuals embrace these tools in a relational situation. The interviews and observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 85 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…A meta-analysis of nearly 300 articles about the relationship between humans and information technologies during the COVID-19 pandemic found that information technologies were mainly used in specific domains like education and employment, and also used in healthcare and daily use ( Vargo et al, 2021 ). A few articles report how OAs have used these technologies for healthcare and family interactions ( Elbaz et al, 2021 ; Racin et al, 2023 ; Tang et al, 2023 ).…”
Section: Related Workmentioning
confidence: 99%
“…A meta-analysis of nearly 300 articles about the relationship between humans and information technologies during the COVID-19 pandemic found that information technologies were mainly used in specific domains like education and employment, and also used in healthcare and daily use ( Vargo et al, 2021 ). A few articles report how OAs have used these technologies for healthcare and family interactions ( Elbaz et al, 2021 ; Racin et al, 2023 ; Tang et al, 2023 ).…”
Section: Related Workmentioning
confidence: 99%